Readability of the American, Canadian, and British Otolaryngology–Head and Neck Surgery Societies' Patient Materials. (May 2022) - Kim, Joo Hyun; Grose, Elysia; Philteos, Justine; Forner, David; Noel, Christopher W.; Wu, Vincent; Eskander, Antoine
Objective: Patient education materials across 3 national English otolaryngology–head and neck surgery (OHNS) societies: the American Academy of Otolaryngology–Head and Neck Surgery (AAO-HNS), the Canadian Society of Otolaryngology–Head and Neck Surgery (CSOHNS), and Ear, Nose, and Throat United Kingdom (ENT UK) were examined to determine whether they are written at a level suitable for patient comprehension. Study Design: Cross-sectional study. Setting: Online patient materials presented through OHNS national societies. Methods: Readability was calculated using the Flesch-Kincaid Grade Level, Flesch-Kincaid Reading Ease Score, and Simple Measure of Gobbledygook Index. All public patient education materials available through the CSOHNS, AAO-HNS, and ENT UK websites were assessed. Patient education materials were grouped into categories by subspecialty. Results: In total, 128 patient materials from the 3 societies were included in the study. All 3 societies required a minimum grade 9 reading comprehension level to understand their online materials. According to Flesch-Kincaid Grade Level, the CSOHNS required a significantly higher reading grade level to comprehend the materials presented when compared to AAO-HNS (11.3 vs 9.9; 95% CI, 0.5-2.4; P < .01) and ENT UK (11.3 vs 9.4; 95% CI, 0.9-2.9; P < .01). Patient education materials related to rhinology were the least readable among all 3 societies. Conclusion: This study suggests that the reading level of the current patient materials presented through 3 national OHNS societies are written at a level that exceeds current recommendations. Promisingly, it highlights an improvement for the readability of patient materials presented through the AAO-HNS.